Advances in the treatment of recurrent aphthous stomatitis: from synthetic and natural drugs to novel drug delivery systems - Kong, Xiangran; Fan, Lin; He, Dawei; Wang, Lin; Sun, Jiang (Frontiers in Pharmacology, 2026)
BackgroundRecurrent aphthous stomatitis (RAS), the most common inflammatory disease of the oral mucosa, has a complex etiology and diverse pathogenesis. To date, no curative treatment exists. Recurrent oral ulcers severely impair patients' quality of life, making the development of highly effective and safe therapeutic strategies an urgent priority in current clinical research.MethodLiterature references were sourced from publications retrieved via searches on GeenMedical, X-mol, CNKI, and PubMed using the search terms “recurrent aphthous stomatitis” OR “recurrent aphthous ulcer” OR “oral ulcer” AND “treatment” in English and Chinese. The focus was on two dimensions: drug types and delivery systems.ResultsSynthetic drugs such as corticosteroids have clear efficacy, but their potential adverse reactions limit their long-term use. In contrast, natural medicinal components such as licorice and quercetin are gaining increasing attention because of their multitarget mechanisms of action, favorable safety profiles, and therapeutic effects. With respect to delivery systems, novel adhesion agents, microneedles, and nanomedicines currently in development have been evaluated. These advantages include prolonged retention time on ulcer surfaces, enhanced biosafety, improved therapeutic efficacy, and current limitations.ConclusionNatural medicines have potential as novel therapeutic options with high efficacy and safety in clinical settings. By enhancing local drug retention and amplifying therapeutic effects, novel delivery systems open new avenues for RAS therapy. Integrating the therapeutic advantages of natural medicines with the precision and sustained-release characteristics of advanced delivery systems represents a key direction for future research.